The Prevalence of von Willebrand Disease and Significance of in Vitro Bleeding Time (PFA-100) in von Willebrand Disease Screening in the İzmir Region - Fatih Şap; Tülay Kavaklı; Kaan Kavaklı; Ceyhun Dizdarer (Turkish Journal of Hematology, 2013)
Objective: von Willebrand disease (vWD) is the most common hereditary bleeding disorder. The purpose of this investigation was to determine the prevalence of vWD among adolescents in İzmir and to assess the sensitivity and specificity of PFA-100 as a screening method in detecting this disease. Material and Methods: Our study was conducted on adolescents in the city of İzmir between October 2006 and March 2007. A total of approximately 1500 high school students between 14 and 19 years of age were planned to be included in the investigation. Survey forms prepared for assessing hemorrhagic diathesis were completed by 1339 individuals (512 males, 827 females). The necessary laboratory tests were performed after having obtained written informed consent from 40 individuals suspected to have hemorrhagic diathesis. Results: Based on the von Willebrand factor antigen (vWF: Ag) and ristocetin cofactor activity (vWF: RCo) levels and bleeding symptoms, vWD type-1 was diagnosed in 14 individuals (4 males, 10 females; prevalence: 1.04%). The most common bleeding symptom in these patients was found to be epistaxis (10/14). Screening with PFA-100 revealed prolongation in both cartridges (Col/ADP and Col/Epi) in 3 of the 14 patients. PFA-100 was determined to exhibit 21.4% sensitivity and 100% specificity in the diagnosis of vWD. Conclusion: The PFA-100 device was found to have high specificity but to have exhibited low sensitivity. Therefore, its utilization as a screening test may be problematic in patients with mild type-1 vWD. Specific tests (vWF: RCo, vWF: Ag) are required for the definite diagnosis of vWD. However, further studies with a large number of patients are needed.